Geology, geochemistry and geochronology of the Boa Sorte Mesoarchean Granite, Água Azul do Norte Municipality, Pará state – Carajás Province - Rodrigues, Daniel Silvestre; Oliveira, Davis Carvalho de; Macambira, Moacir José Buenano (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
The Boa Sorte granite occurs in the Transition Subdomain between the Rio Maria domain and the Carajás basin. It is an E-W elongated batholith, mainly composed of biotite leucomonzogranites showing different degrees of deformation, whose emplacement occurred at least 2857 ± 2 Ma (zircon Pb-Pb). To the southern, it is in contact with the Água Limpa granodiorite, is intrusive into TTG and greenstone belts sequence, and is intruded by mafic to intermediate rocks akin to those of Pium Diopside-Norite and by plutons of the Planalto intrusive suite. Geochemically, they are calk-alcaline, weakly peraluminous, I-type granites, where four rock groups were identified: 1) High La/Yb – characterized by high (La/Yb)N ratios and moderate negative Eu anomalies; 2) Low La/Yb – low (La/Yb)N ratios and strong negative Eu anomalies; 3) Low Gd/Yb – depleted in light rare earth elements (REE) contents, with (Gd/Yb)N ratios close to unity, and moderate negative Eu anomalies; and 4) Low ΣREE – characterized by low total REE contents, with high to moderate (La/Yb)N ratios. Such groups could be correlated to the leucogranitic bodies of the Canaã dos Carajás area, suggesting that both regions were affected by similar magmatic processes during the Mesoarchean evolution of the Transition Subdomain.
Keywords: Carajás province; Mesoarchean; Leucogranites; REE; Pb-Pb and U-Pb Zircon Geochronology